1985
DOI: 10.1093/infdis/151.6.1130
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Praziquantel on Different Developmental Stages of Schistosoma mansoni in Vitro and in Vivo

Abstract: To discern whether stage-specific resistance of Schistosoma mansoni to praziquantel occurs in vitro, we determined minimal effective concentrations (MECs) of drug needed to increase motor activity, produce contraction and/or paralysis, and cause tegumental vesiculation of developmental stages from day 0 to day 42 of S. mansoni. Recovery of these stages from exposure to praziquantel in vitro was also evaluated. MECs of praziquantel inducing increased motor activity and muscular contraction or paralysis or both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
122
1
7

Year Published

1986
1986
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(137 citation statements)
references
References 15 publications
7
122
1
7
Order By: Relevance
“…The slightly lower susceptibility of adult S. mansoni worms than NTS to artesunate might be due to the lack of hemin, a primary activator of the peroxide group, in the incubation medium (41). Overall, the findings on the individual parasite stages are consistent with previous in vitro studies with these drugs (2,10,24,27,40).…”
Section: Vol 49 2011 Microcalorimetry To Study Antischistosomal Drusupporting
confidence: 89%
“…The slightly lower susceptibility of adult S. mansoni worms than NTS to artesunate might be due to the lack of hemin, a primary activator of the peroxide group, in the incubation medium (41). Overall, the findings on the individual parasite stages are consistent with previous in vitro studies with these drugs (2,10,24,27,40).…”
Section: Vol 49 2011 Microcalorimetry To Study Antischistosomal Drusupporting
confidence: 89%
“…In areas with heavy transmission of schistosomiasis, it has been suggested that people might have been infected in the previous 3-5 weeks. Hence, such patients would harbor immature schistosomes that are less susceptible to PZQ [7,[39][40][41] . These immature stages have the high chance to survive a single treatment and mature to deposit eggs in the subsequent weeks.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for the lingering worm DNA detection may have been unsatisfactory treatment. Immature ova/ worms are refractory to PZQ treatment (11)(12)(13)(14). Multiple treatments with PZQ are needed with intervals between the treatments to allow maturation of immature worms/ova (2 to 4 weeks) (13)(14)(15).…”
mentioning
confidence: 99%